A medical language for climate discourse - Forgács, Bálint (Frontiers in Climate, 2024)
Innovative communication theories propose that we do not understand messages by decoding their meaning, but we figure out meaning by inferring what the speaker intended to express. However scientifically accurate the messages climate scientists have put forward, the appropriate inferences may not have been drawn by most of their audiences. One of the main reasons may be that scientific metaphors allow for multiple interpretations, yet, because of their expressive power, they impact discourses disproportionately. Climate communication took a path of euphemistic scientific expressions partially due to the noble scientific norms of self-restraint and modesty, but the hidden implications of climate jargon distort the way nonexperts think about the heating climate. Consequently, the current climate jargon hinders informed decisions about the fate of Earth's life support systems. Changing the softened expressions of climate language, from the cool of basic research to the heat and compassion of medical contexts, may allow for more productive public and political debates -that may lead to more powerful policy solutions. Speaking and thinking in medical terms could turn the perception of worst case scenarios from hypothetical doomism to life-saving interventions. We typically start reducing fever before it gets out of control, let alone crosses a threshold of potential death. Instead of putting on a positivist mascara, a calm and serious discussion of safety measures in medical terms, for example, experimentation with unknown biological-climatic thresholds, could foster a more honest evaluation of the required legal and regulatory steps to keep our home planet habitable.